Dose-adjusted Plasma Concentrations of Sublingual Buprenorphine are Lower During than After Pregnancy. Issue 4 (December 2017) - Bastian, J.R.; Chen, H.; Zhang, H.; Rothenberger, S.; Tarter, R.; English, D.; Venkataramanan, R.; Caritis, S.N.
Abstract : ( Am J Obstet Gynecol . 2017;216(1):64.e1–64.e7) Buprenorphine is increasingly used in pregnant women with opioid use disorders, as it has recently been associated with less severe neonatal complications and comparable efficacy as methadone. Currently, dosing of buprenorphine for pregnant women is based on recommendations for nonpregnant patients; however, drug absorption and metabolism can be impacted by pregnancy. This study examined the pharmacokinetic properties of sublingual buprenorphine in pregnant women and the postpartum period.